Multi Parameter FEM Optimisation of I.C. Engine V-Twin Valve Spring Compression Tool - Josip Cumin; Dejan Marić; Daniel Novoselović; Tomislav Šolić (Tehnički Vjesnik)
This article deals with FEM optimization of valve spring compression tool. The new modified tool presented here is advanced in design and features (as opposed to the later one). The presented tool design is made with goal of higher tool rigidity, lower mass, lower material cost, easier manipulation in cramped space and easier positioning on the cylinder head. The three parameters varied on three levels - design of experiments was utilized for the observation of response in the form of equivalent stress and maximal allowable displacement of the tool base material. Statistical analysis shows influential factors for the proposed mathematical models. In the last part of the paper, the tool with optimal parameters, stresses and maximal displacement is shown.It was concluded that S355J2 material with thickness of 5 mm is optimal for the tool construction due to the relatively high yielding stress as opposed to calculated stresses in the spring compression tool itself, and it gives a reasonably small elastic displacement of the tool which is not critical for the maintenance job itself.